An Observational Study of Physicians' Workflow Interruptions in Outpatient Departments in China - Zhu, Ximin; Hu, Yinhuan; Wang, Liuming; Li, Dehe; Wu, Xiaoyue; Xia, Shixiao; Cheng, Siyu (Frontiers in Public Health, 2022)
Background: Workflow interruptions are frequent in hospital outpatient clinics. Eventually, not only reducing the work efficiency and quality, but also further threatening patient safety. Over the last 10–15 years, research on workflow interruptions in inpatient care has increased, but there is a lack of research on the interruptions in outpatient clinics. The present study aimed to study the differences in physicians' workflow interruptions among outpatient departments in the tertiary hospital in China. Methods: In a tertiary hospital, a standardized observational study of 32 doctors' workflow in outpatient department of four typical clinical specialties was conducted. The record of workflow interruptions was based on a self-made observation instrument after verifying its reliability and validity. Linear regression methods were used to assess outpatient characteristics as predictors of the number of interruptions. The Kruskal-Wallis test was used to analyze the difference about the duration of interruptions among specialties, and the Chi-Square Test was used to examine the sources of interruptions among different specialties, to determine whether interruption source is associated with specialty. Results: The number of patients was the significant independent predictor of the number of interruptions(p<0.001). In terms of work tasks being interrupted, the highest interruption rate occurred when physicians were asking health history: 19.95 interruptions per hour. The distribution of interruption sources among the four clinical specialties were statistically different (Χ2 =16.988, p = 0.049). Conclusion: The findings indicate that physicians' workflow interruptions are connected with many contents in the work system. Further emphasis should be placed on the effective application of hospital management measures in an interrupted environment to promote a safe and efficiency outpatient care.